1999
DOI: 10.1177/070674379904400504
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Assertive Community Treatment: A Review of the Literature

Abstract: (Can J Psychiatry 1999;44:443-454)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(118 citation statements)
references
References 61 publications
3
108
0
7
Order By: Relevance
“…Latimer found that higher fidelity programs reduced hospital days 23 percent more than lower fidelity programs [27]. But, he cautioned that as mental health systems rely less on hospitals over time, the cost advantages of ACT will be harder to achieve and justification for the model will need to be based more on its clinical benefits.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Latimer found that higher fidelity programs reduced hospital days 23 percent more than lower fidelity programs [27]. But, he cautioned that as mental health systems rely less on hospitals over time, the cost advantages of ACT will be harder to achieve and justification for the model will need to be based more on its clinical benefits.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Most studies conclude that ACT teams likely produce more effective outcomes if their measured fidelity is higher [27]; that is, if they squarely meet more DACTS criteria.…”
Section: Individual Versus Team Case Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…community treatment Fidelity to evidence-based models of care has been shown to predict better clinical outcomes for several types of practices (Cuddeback et al, 2013;Drake, Bond, & Essock, 2009;Latimer, 1999;J. H. McGrew, Bond, Dietzen, & Salyers, 1994;McGuire et al, in press; McHugo, Drake, Teague, & Xie, 1999;van Vugt et al, 2011).…”
mentioning
confidence: 99%
“…The model has been tested all over the world and similar results have been found [42][43][44][45]. ACT's effect on other outcomes (e.g., employment, living arrangements, etc.)…”
Section: What Does Research Evidence Indicate?mentioning
confidence: 55%